2020
DOI: 10.1186/s13317-020-00139-9
|View full text |Cite
|
Sign up to set email alerts
|

Current laboratory and clinical practices in reporting and interpreting anti-nuclear antibody indirect immunofluorescence (ANA IIF) patterns: results of an international survey

Abstract: Background The International Consensus on Antinuclear Antibody (ANA) Patterns (ICAP) has recently proposed nomenclature in order to harmonize ANA indirect immunofluorescence (IIF) pattern reporting. ICAP distinguishes competent-level from expert-level patterns. A survey was organized to evaluate reporting, familiarity, and considered clinical value of ANA IIF patterns. Methods Two surveys were distributed by European Autoimmunity Standardization In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In the recent past, autoantibody testing for systemic rheumatic diseases has been revolutionized [9]. The integrated approach of ANA patterns and extended panels of ANA-speci c antibodies have both reduced the time-lapse in diagnosing the disease and misdiagnosis [10]. Moreover, the Interpretation and reporting of ANA have been standardized to reduce subjectivity [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, autoantibody testing for systemic rheumatic diseases has been revolutionized [9]. The integrated approach of ANA patterns and extended panels of ANA-speci c antibodies have both reduced the time-lapse in diagnosing the disease and misdiagnosis [10]. Moreover, the Interpretation and reporting of ANA have been standardized to reduce subjectivity [11].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, reported in patients with interstitial cystitis, later studies observed this pattern in a wide spectrum of clinical conditions, such as chronic inflammation, asthma, atopic dermatitis, autoimmune thyroiditis, as well as in apparently healthy individuals ( 25 , 26 ). Despite sharing morphological similarity with the nuclear homogeneous pattern (AC-01), the DFS pattern has a completely different clinical significance that needs to be clarified ( 27 ). To date, the DFS pattern has mainly been linked to anti-DFS70 antibodies in various studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, autoantibody testing for systemic rheumatic diseases has been revolutionized [9]. The integrated approach of ANA patterns and extended panels of anti-ENA antibodies have both reduced the time-lapse in diagnosing the disease and misdiagnosis [10]. Moreover, the Interpretation and reporting of ANA have been standardized to reduce subjectivity [11].…”
Section: Discussionmentioning
confidence: 99%
“…A very important factor is clinicians' understanding and acceptance of the revised reporting format of these autoantibodies. As they are familiar and more comfortable with the ANA test results and interpretation, introducing the concept of anti-cellular antibodies (ACA) with the importance of anti-cytoplasmic antibodies and anti-mitotic antibodies will require their continuous education [10,13].…”
Section: Discussionmentioning
confidence: 99%